PERANCANGAN APLIKASI PEMESANAN PLASTIK BERBASIS WEB (BUSINESS TO CUSTOMER) PADA PT ALIENE EXPRINT PLASTIK - Meika Alfiat; Yunus (CV. Multi Kreasi Media, 2024)
As orders have increased from one of the plastic companies PT Aliene Exprint Plastic in Tangerang, in this Case study I am trying to help the company to improve services to its customers to be able to order plastics through the application without having to come to PT Aliene Exprint Plastic, and it is hoped that they will be able to. increase company turnover. With the increasing number of internet Users nowadays, I chose to implement this system on a web platform. One way to get around this is to create abased Plastic Ordering Application Web. The process of running this application later the customer will access the web from the company PT Aliene Exprint Plastic starting from Chart, Checkout, Form Contact, Login / Register, Admin Access Rights, Payments etc. Which later will make it easier customers forto place orders. Customer can choose and order the plastic in accordance with his wishes meng-input rightsome data that will be addressed by the admin and will be sent payment details. The development method that will be Used to design this application is themethod Extreme Programming.